Analisis Kelayakan Usahatani Padi Di Desa Mojopetung Kecamatan Dukun Kabupaten Gresik - Wahyu Dinul Muzainan; I Made Suparta (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research explains the level of feasibility of rice farming in Mojopetung village, Dukun sub-district, Gresik district. This business is engaged in rice production. This research uses a descriptive analysis method which uses 7 informants from rice farming owners as research subjects. Data collected through interviews aims to analyze fixed costs, total costs, variable costs, demand and profits. The feasibility of the business carried out is by using the R/C Ratio (Revenue Cost Ratio, B/C Ratio (Benefit Cost Ratio), BEP (Break Even Point) calculation in order to find out whether the business is feasible or not. The results of this research can provide education for business people about the continuation of rice farming in the village of Mojopetung, Dukun Gresik.